2011
DOI: 10.1203/pdr.0b013e31820263e7
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cow's Milk Protein-Specific Inflammatory and Regulatory Cytokine Responses in Preterm Infants With Necrotizing Enterocolitis and Sepsis

Abstract: Enteral feeding with cow's milk formula is associated with neonatal necrotizing enterocolitis (NEC) and sepsis. Dietary antigen sensitization may play a role in promoting and/or sustaining inflammation in both conditions. Aiming at investigating cow's milk protein (CMP)-specific cytokine responses in preterm infants with NEC and sepsis, 14 babies with NEC, 14 matched healthy controls, and 10 septic controls were recruited. Unstimulated and stimulated peripheral blood mononuclear cells (PBMCs) secreting IFN-␥, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Furthermore, increased intestinal permeability may facilitate translocation of intestinal bacteria, thereby increasing the infants’ susceptibility to sepsis. Abdelhamid et al [12] recently showed that the blood mononuclear cells of infants with sepsis or NEC have an enhanced pro-inflammatory cytokine response upon stimulation with bovine casein when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased intestinal permeability may facilitate translocation of intestinal bacteria, thereby increasing the infants’ susceptibility to sepsis. Abdelhamid et al [12] recently showed that the blood mononuclear cells of infants with sepsis or NEC have an enhanced pro-inflammatory cytokine response upon stimulation with bovine casein when compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a small human study, PBMCs isolated from stage II and III NEC infants at diagnosis exhibited 3-fold more cells spontaneously secreting IL-4 than GA-matched healthy controls (Ref. 138). However, comparing pre-operative NEC infants and GA-matched controls, serum IL-4 was not different, while IL-5 was 50% lower (Ref.…”
Section: Th2 Cytokinesmentioning
confidence: 93%
“…RBC transfusion may also interrupt the mesenteric vascular tone via an imbalance of nitric oxide and endothelin-1, stimulating the production of pro-inflammatory cytokines as occurs during multiple organ failure22). Recently, several in vitro studies have reported that sensitization to cow milk proteins may be involved in NEC pathogenesis23,24). At present, however, data are insufficient to determine the involvement of these factors in the pathogenesis of NEC.…”
Section: Pathogenesismentioning
confidence: 99%